Golden Bear Returns to Vallejo - Vallejo News Chronicle (Vallejo News Chronicle)
California's flagship, the Golden Bear, slides into its berth at Morrow Cove at noon today after a 9,000 mile cruise in the Pacific with 131 midshipmen and 44 officers of the California Maritime Academy.